2020
DOI: 10.1063/1.5143972
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and broad-range thickness estimation method of hexagonal boron nitride using Raman spectroscopy and optical microscope

Abstract: Hexagonal boron nitride (hBN) has drawn great attention for its versatile applications in electronics and photonics, and precise estimation of its thickness is critical in many situations. We propose a rapid and broad range (10–500 nm) in situ thickness estimation method for transparent hBN and SiO2 layers on the Si substrate using Raman peak intensity ratios at two wavenumbers and optical microscopy image analysis. We theoretically and experimentally demonstrate our method for a wide range of hBN layer thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The EQE for monochromatic illumination with an incident photon energy of hν (h = Planck constant, ν = light frequency) can be expressed as The position-dependent photon absorption profile in the Pt layer, P abs (x), should be considered as shown in Figure 3a, and it can be obtained using a transfer matrix method or theoretical calculation. 31,32 Because only hot electrons with sufficient energy (E m > qΦ B ) have a chance to overcome the barrier, the distribution of generated hot carriers, P dis (E m ), should be considered as shown in Figure 3b. We employed the energy distribution of joint density of states (EDJDOS) for the optically excited electrons in the absorption metal (Pt) layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The EQE for monochromatic illumination with an incident photon energy of hν (h = Planck constant, ν = light frequency) can be expressed as The position-dependent photon absorption profile in the Pt layer, P abs (x), should be considered as shown in Figure 3a, and it can be obtained using a transfer matrix method or theoretical calculation. 31,32 Because only hot electrons with sufficient energy (E m > qΦ B ) have a chance to overcome the barrier, the distribution of generated hot carriers, P dis (E m ), should be considered as shown in Figure 3b. We employed the energy distribution of joint density of states (EDJDOS) for the optically excited electrons in the absorption metal (Pt) layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 3j shows the abundance map of flakes A1−E1 in a single calculation using 50 and hBN. 51,52 Therefore, by building the relation between the optical contrast of monolayer 2D materials and the oxidation thickness of the substrate, monolayer 2D flakes can be distinguished in an optimized way, especially for hBN with low contrast, which should be conducted in the following work.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To measure monolayer hBN flakes, the optical contrast should be maximized for the best imaging performance. It has been reported that the optical contrast varies with the change of the thickness of SiO 2 for graphene, , MoS 2 , and hBN. , Therefore, by building the relation between the optical contrast of monolayer 2D materials and the oxidation thickness of the substrate, monolayer 2D flakes can be distinguished in an optimized way, especially for hBN with low contrast, which should be conducted in the following work.…”
Section: Resultsmentioning
confidence: 99%
“…So far, a variety of thickness identification techniques of 2D nanofilms have been exploited, including atomic force microscopy (AFM), [12] scanning electron microscopy (SEM), [24] transmission electron microscopy (TEM), [25] scanning tunnelling microscopy (STM), [26] Raman spectroscopy, [27][28][29] photoluminescence (PL) spectroscopy, [5] and optical microscopy (OM). [24,[30][31][32][33][34][35][36][37][38][39][40] Among these techniques, AFM is most widely used to directly measure the thickness of 2D nanoflakes with small size, but it is time-consuming and low-throughput for large area films. Moreover, AFM is a contact method that can potentially induce structural defects [41] and the measured results might be affected by the absorbed water layer.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, Optical microscopy (OM) is a simple, reliable, non-contact and non-destructive technique that enables rapid and high-throughput characterization of large area 2D nanofilms. The OM method is mainly divided into two categories: [45] one is based on the apparent color of the samples [24,[30][31][32][33] and the other is based on optical contrast. [34][35][36][37][38][39][40] The color-based OM approach requires complex calculations and depends sensitively on the light source and the substrate.…”
Section: Introductionmentioning
confidence: 99%